The crying game [videorecording (DVD)] - Jordan, Neil, 1950-; Woolley, Stephen; Richardson, Miranda; Rea, Stephen; Davidson, Jaye; Whitaker, Forest (Lionsgate, 2014)
An unlikely kind of friendship develops between Fergus, an Irish Republican Army volunteer, and Jody, a kidnapped British soldier lured into an IRA trap by another IRA member. When the hostage-taking ends up going horribly wrong, Fergus escapes and heads to London, where he seeks out Jody's lover, a hairdresser named Dil. Fergus changes his name and gets a job as a day laborer. His starts seeing Dil, who knows nothing about Fergus' real background. But there are some things about Dil that Fergus does not know either.